Educational Strategies in Wildlife Control at Airports as an Optimisation of Safety Management - M Indra Martadinata; Yeti Komalasari; Ahmad Bahrawi; M Efaldes Syahputra (International Journal of Educational Review, 2023)
One of the factors that can cause an aircraft accident is the presence of wildlife at the airport. Wildlife can pose a threat to aviation safety if not managed properly. The purpose of this research is to analyze the education strategy for controlling wildlife at the airport as a form of safety management optimization to find out what the inhibiting factors and supporting factors in handling wildlife to get the right wildlife control pattern.  This research method is descriptive research with a qualitative approach where researchers seek supporting data by conducting interviews, observations and some document literacy from the airport studied, namely Muhammad Taufiq Kiemas Airport in West Pesisir Regency, Lampung Province. This research resulted in several findings that there are inhibiting factors, namely the absence of a wildlife hazard control unit at the airport so that the handling of wildlife does not have a planned and programmed standard procedure. However, there are several supporting factors, namely operational officers already know the types of wildlife and the causes of the gathering of wildlife around the airport. Facilities available at the airport such as perimeter fences can prevent and limit wildlife entering the airport from wild boar, monkeys, and apes. Handling of wild birds is done by traditional capture and not by the guidelines. Coordination and communication between the airport and Air Navigation are well-established and mutually supportive of wildlife control activities during operational hours. The results of this study are not only useful for the airport but also for the beginning of the development of further research on wildlife control. This research has a novelty, namely the steps of controlling wildlife at the airport and educational strategies in controlling wildlife as an optimization of safety management.